Evaluasi Penerapan Pusat Kapabilitas Internasional Telkom Indonesia Dalam Mengembangkan Talenta Global - Muhammad, Irsyad; Fachira, Ira (Journal of Business and Management, 2020)
Abstract. As the world becomes more and more connected due to globalization and various other factors, the demand of employees with global talent also increases. In 2014 Telkom Indonesia took an initiative to develop global talent for its employees due to the current international expansion they were going to conduct. Telkom International Capability Center was one of the program of the initiative which acts as the enabler for the whole thing, like its name it is a center dedicated to all affair related with international capability development. Specifically it was a center used to enhance employee’s skills and knowledge for international assignment by leveraging their global talent. It was quite effective seen from the fact that Telkom’s international expansion was successful without the need to hire a significant amount of expatriates. However with the progress of technology and new challenges in today’s world the Telkom International Capability Center has not been updated and reevaluated. The research interviewed key individuals with big involvement with Telkom International Capability Center to analyze the things which are needed to be changed in order to stay relevant and effective in its method to develop global talent, the research also conducts literature review to corroborate the findings from the interview. There were in fact a couple of things that needed to be changed such as the increased use of technological tools is needed to ensure a more efficient outcome, gamification also plays a big part to make certain that the participants is enthusiastic, the increased continuity of knowledge and feedback, and other minor adjustments. The researcher aims that it would benefit not only PT. Telkom but all other companies which are going through a similar condition. All things considered the researcher hopes that it could benefit Indonesia in enhancing their workforce in order to contribute the efforts of becoming a developed nation.Keywords: Globalization, Global Talent, Capability Center